IMPROVEMENT OF ORGANIZATIONAL AND ECONOMIC MECHANISM OF STABLE DEVELOPMENT OF THE ENTERPRISE OF THE REGION METALLURGICAL BRANCH - V. E. Sidorchuk; Yu. N. Masalsk; D. L. Konovalov (Литьë и металлургия)
The problem of guaranteeing a sustainable development, role and place of the enterprise in this process is revealed in this article. The special attention is paid to the methods of integral assessment of development stability by overall index.